Optimization of Design Parameters of Spacecraft Equipped with Electro Rocket Low-thrust Engine and Calculation its Applying Area at Low Earth Orbit. (2017) - Ishkov, Sergey A.
Abstract: The problem of electro rocket engine type and its main design parameters optimization for spacecraft located at low circular Earth orbit is studied. The efficiency of chemical (impulse) and electro rocket engine of low-thrust is analyzed. Introduced criteria of efficiency – payload mass maximization, introduced assumption that engine exhaust velocity is constant. In accordance with criteria and assumption, the analytical solution for spacecraft design parameters of spacecraft is obtained. Also, analytical solution for area of efficiency of electro rocket low-thrust engine is obtained. Calculation of spacecraft design parameters equipped with electro rocket low-thrust engine and area of its efficiency applying is carried out.